The Abrogation Issue in Verses of Night Prayer: Applied Study - Al-Mawadiya, Hanin Khalaf (Journal of Islamic Sciences, 2024)
This research includes introduction, preface, one requirement, conclusion and indexes.The introduction includes: the importance of research, research objectives, research problem, previous studies, research methodology,, justifications for selecting a topic, and research plan.As for the first requirement: it is also an applied analytical study of the transcription claim in the verses of Qiyam al-Layl - Surat Al-Muzzammil, and it deals with it; the transcript verse, the opinions of those who say transcription, and the opinions of those who say that it is not with the statement and clarification of the proper approach in understanding this invalid claim and the words of the Lord of Glory.As for the conclusion, it contains the most important results of the recommendations that I reached through writing this research.The indexes included verses, sources and topics.And Praise be to Allah, the Lord of the Worlds
Keywords: Abrogation; Night Prayer Verses